Asymptotics for randomly weighted and stopped dependent sums. Issue 2 (17th February 2016) - Yang, Yang; Leipus, Remigijus; Šiaulys, Jonas
Abstract : This paper deals with the tail probability of, where is a sequence of extended negatively upper orthant dependent or bivariate upper tail independent, identically distributed random variables with dominatedly varying tails, is a sequence of nonnegative nondegenerate at zero random variables (not necessarily independent and identically distributed), is a random variable taking values in . In addition, , and are mutually independent. Under some mild conditions, the weak asymptotic equivalence relations for the probability are established. An application to the random-time ruin probability in the discrete time risk model is provided.